Prediction of emotional intelligence on the basis of executive functions and metacognitive awareness among female - Sarvarian, Zahra; Mirzaei, Hanifeh; Jahed, Zohreh Ghaffari (International Journal of Applied Behavioral Sciences, 2018)
Background: the aim of this correlational study was to predict emotional intelligence according to executive functions and metacognitive awareness in junior high school female students.Method: the study sample consisted of 182 secondary school female students at District 2, Tehran, Iran, who were selected using multi-stage random sampling method. The Wisconsin Card Sorting Test (WCST), Schutte Self-Report Emotional Intelligence Test (SSEIT) and Metacognitions Questionnaire (MCQ) (2006) were used to collect data. In order to analyze the data, in addition to descriptive statistics methods, simultaneous multiple regression analysis was implemented using the SPSS statistical software.Results: the results showed that 39.9% of the variance in emotional intelligence can be accounted for based on linear combination of variables from executive functions, including number of classes, preservation error and other errors, and variables from metacognitive awareness, including planning/assessment and personal knowledge. These results could have numerous tacit applications in planning to prevent negative consequences of problems caused by weakness in executive functions and metacognitive awareness.